PENGGUNAAN FAKTOR AGAMA OLEH PEMERINTAH INDONESIA DALAM UPAYA PEMBEBASAN SANDERA ANAK BUAH KAPAL PANDU BRAHMA 12 DI FILIPINA TAHUN 2016 - Wiwin Sutaryani, Ni Made; Fasisaka, Idin; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
The hostage of Indonesian citizens which conducted by the Abu Sayyaf group was closely related to the coal export by Indonesia to the Philippine as the main source in fulfilling energy. The hostage was taking occurred in the water of Sulu on March 25, 2016 involves 10 crews of tugboat Pandu Brahma 12 which departed from south Kalimantan to the Philippine on March 15, 2016. In this case the parties of the hostage-taker asked for ransom of 50 million pesos or equivalent with 15 milliard rupiahs and the hostages were taken to its hideout in the Sulu archipelago. At first, the company of tugboat Pandu Brahma 12 has prepared the money for ransom but the Ministry of Foreign Affair of Indonesia, Retno Marsudi decided to take the diplomatic way which use religion as the factor to divest the hostages by sending the negotiator teams. This is done based on the similarity of cultures and values, especially religion between Indonesia and the southern of Philippine. Keywords : hostage, tugboat Pandu Brahma 12, Abu Sayyaf group, negotiator team.